Prosedur Kearsipan di Bagian Pemeriksaan pada Kantor Pelayanan Pajak Pratama Bekasi Selatan - Atika .; Neneng Fauziah (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
From the observation, archival procedures in Inspection Tax Pratama Office at Bekasi Selatan run well. However, there are several obstacles faced such as the absence of officer assigned in for letters administration, creating confusion. Archival procedures in Section Inspection Tax Pratama Office Bekasi Selatan is procedures of incoming mail and outgoing mail archival procedures. Procedures of incoming mail are receiving, recording and controlling, distribution, and storage. The outgoing mail archival procedures are processing, recording and controlling, storage, and shipping. Some letters stored at Affairs Secretariat staffing is letters (holiday leave, absentee, maternity leave, retired), technical assistance, security, law entrance to the head, and others. Recording the incoming and outgoing mail uses control card. Mail storage system uses decentralized systems and index system applied in system subjects. The facilities used for archival storage are folders, archive shelves, filing cabinets, and file box